Supply Chain Risk Management and Financial Performance: Empirical Study of Manufacturing Companies in Southeast Asia - Rizal Perlambang; Rashid Rahman; Aiman Fariq (Journal Markcount Finance, 2025)
Supply chain risk management (SCRM) has become a critical concern for manufacturing companies, particularly in Southeast Asia, where globalization and market volatility pose significant challenges. Effective SCRM is essential for maintaining operational stability and achieving financial performance. However, empirical evidence on the relationship between SCRM practices and financial outcomes in this region remains limited. This study aims to investigate the impact of supply chain risk management on the financial performance of manufacturing companies in Southeast Asia, providing insights into how SCRM practices can enhance profitability and resilience. A quantitative research design was employed, utilizing survey data collected from 250 manufacturing companies across Southeast Asia. Structural equation modeling (SEM) was used to analyze the relationships between SCRM practices and financial performance indicators, such as return on assets (ROA) and profit margins. The findings reveal that effective SCRM practices, including risk identification, assessment, and mitigation, significantly improve financial performance. Companies with robust SCRM systems reported higher profitability and greater resilience to disruptions. Risk mitigation strategies, in particular, were found to have the strongest positive impact on financial outcomes. This study highlights the importance of implementing comprehensive SCRM practices to enhance financial performance in the manufacturing sector.